Real-Time Traffic Study Using Smart Technology - Kannadasan B. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The concomitant spike in traffic creates substantial obstacles to effective traffic management as metropolitan areas experience rapid development. This article details an innovative project in the Australian city of Liverpool that uses smart visual sensors to conduct a real-time traffic study. To monitor various forms of transportation in real-time while protecting the privacy of individuals, these sensors were created as a pilot project and use computer vision and deep neural networks. The study used a complete town center dataset to evaluate the edge-computing device's performance. We present the Agnosticity Framework, an open-standards system that can read and write data from various sensors. Two experimental results show that the framework improves our general understanding and control of urban traffic dynamics. This research provides important insights for future smart city projects and helps create intelligent and privacy-conscious solutions for urban traffic studies.